Raymond Williams on television : selected writings - Williams, Raymond (Routledge revivals., 2011)
First Published in 1989, this work is based around a monthly TV column which Raymond Williams wrote for The Listener between 1968 and 1972. Those were the years of the Prague Spring, of anti-Vietnam war demonstrations, of fighting in Cambodia and Northern Ireland, of hope for McGovern in the United States and attacks on the Wilson Labour Government in Britain. In The Listener articles Williams comments on all of these events, providing a rare glimpse not only into the events of his daily life but also into the continuing development of a personal sociology of culture.